Students’ perceptions of using Google Meet in English online learning at Muhammadiyah Nitikan Elementary School - Soviyah, Soviyah; Puspita, Linda; Altawil, Abdulmohsin Nasser (Universitas Ahmad Dahlan, 2023)
Google Meet is a new medium used for students and teachers in learning during COVID-19 pandemic. At Muhammadiyah Nitikan Elementary School, English learning has been carried out online by utilizing online mediums in the learning process. By using Google Meet as an alternative learning medium, students at Muhammadiyah Nitikan Elementary School have various opinions on its use. The objective of this research was to find out students’ perceptions of using Google Meet in English online learning. The research method in this research was quantitative method. The participants of this research were sixth grade students of Muhammadiyah Nitikan Elementary School consisting of 88 students, 46 female students and 42 male students. The sampling used in this research was random sampling. Questionnaire is used to collect the data which is then analyzed using quantitative methods. The results of this study showed that out of a total of 88 participants, 1 student (1.14%) has a very positive perception, 35 students (39.77%) have a positive perception, 27 students (30.68%) have a neutral perception, 17 students (19.32%) have a negative perception, and 8 students (9.09%) have a very negative perception.